Inducing differentiation of human dental pulp cells toward acinar-lineage - Yan, Ming (Am J Transl Res, 2020)
Objective: To induce acinar-differentiation from human dental pulp cells for potential application in aiding treatment of dry-eye syndromes. Method: Human dental pulp cells were co-cultured with human submandibular gland acinar cells using a transwell construction for 2 weeks. The two populations of cells were physically separated while chemical and biochemical components can be exchanged. Fibroblasts were included as a negative control. Expression of amylase, cytokeratin 8 and vimentin were examined by immune-staining. Amylase activity was measured using an AMS Assay Kit. Result: Cobblestone-like islands, a feature of acinar cells, appeared in the dental pulp cells which were co-cultured with salivary gland cells for one week and increased in number and size after two weeks. Antibody detected amylase in 30 and 50% of the pulp cells 1 and 2 weeks in the co-culture, respectively. Cytokeratin 8 increased while vimentin decreased. All these changes indicate an acinar-like differentiation of the dental pulp cells. None of these changes were observed in fibroblasts which were also co-cultured with salivary gland cells, indicating that the acinar-like differentiation is specific for the dental pulp cells. Neither of the changes were observed in dental pulp cells when not co-cultured with the salivary gland cells, indicating that induction is specific and essential. Conclusions: Human dental pulp cells have the potential to differentiate into acinar-like cells which may provide an autologous source for cellular therapy for dry-eye syndromes.